Addition of Phosphorus and Nitrogen Support the Invasiveness of Alternanthera Philoxeroides Under Water Stress. Issue 9 (12th July 2020) - Sun, Jianfan; Javed, Qaiser; Azeem, Ahmad; Ullah, Muhammad Saif; Rasool, Ghulam; Du, Daolin
Abstract: Coordination of plant functional traits with changes in the environment is helpful to understand the mechanisms underlying both invasiveness and adaptation of plants. Thus, to investigate the performance and functional traits in invasive Alternanthera philoxeroides (Mart.), an experiment of water stress is conducted with different nutrient concentrations. Alternanthera philoxeroides plants are grown under natural and nutrient soils and subjected to three levels of nitrogen (N) and phosphorus (P) solution: ambient P and N concentration (P−N−), P addition with an ambient N concentration (P+N−), and P addition with high N concentration (P+N+) in combination with three different irrigation water levels as 1) 100% irrigation, 2) 50% irrigation, and 3) 25% deficit irrigation. Based on results, A. philoxeroides produces significantly higher biomass in both soils under 100% irrigation with P+N− treatment and exhibits higher values of leaf area and root length. However, 25% irrigation with P−N− treatment in both soils exerts a significant negative effect on relative growth rate and root/shoot ratio of A. philoxeroides plants. Under 50% irrigation in soils with both P+N− and P+N+ treatments, high values of leaf nitrogen are recorded. Moreover, nutrient soil is more supportive to A. philoxeroides than natural soil. Abstract : Functional traits of Alternanthera philoxeroides are determined in response to water availability with different nutrient concentrations in different soil types. According to results, nutrients habe a positive effect and are found supportive to invasive A. philoxeroides when suffering from water deficiency. Moreover, nutrient soil facilitates A. philoxeroides growth under water and nutrient deficit conditions.